An evaluation of mobile medical applications for diabetes mellitus - Izahar, Syarafina (2016)
The concept of diabetes mellitus patient self-care, such as the use of mobile applications or "apps," has proved to be beneficial for patients. The concept of self-care is regarding the active involvement of patients in their own care and modifying their lifestyle behaviours. Recent evidence shows that the smartphone interventions may support diabetes self-management. However, the awareness among diabetic patients about the beneficial uses of mobile apps in diabetes mellitus self-management is still lacking and selecting the most appropriate apps for oneself would be challenging for patients, as there are numerous choices of apps available in the apps' store. To evaluate the contents and features of mobile medical applications for diabetes self-management. Two approaches of study design used were systematic review of previous literature about mobile medical applications for self-management of diabetes mellitus and quality assessment of the selected mobile medical applications. Previous literatures about mobile medical applications for self-management of diabetes mellitus were reviewed systematically according to the eight common contents provided in diabetes self-management mobile medical applications. From the eight common contents, there were seven self-monitoring contents provided by the mobile apps, which are self-monitoring blood glucose, self-monitoring weight, self-monitoring physical activity, self monitoring diet, self-monitoring insulin, self-monitoring medication, and self-monitoring blood pressure. Another content is the education for diabetes self-management. There were 16% of the total diabetes· apps found in Apple Apps Store and 7. 72% of the total diabetes apps found in Google Play selected and scored according to eight features. The highest score obtained was five and the lowest was three. The study has shown that there was a multitude of literatures proposed that the contents of diabetes mobile applications such as self-monitoring blood glucose and others are generally useful to both patients and health-care professionals. The interventions of smartphone in supporting self-care and monitoring blood glucose are found to be more beneficial than other computer-based tools. There were numerous choices of mobile applications for diabetes self-management in Apple Apps Store and Google Play, which offer variety of features for managing diabetes. Patients' choices of mobile applications as a platform in managing their diabetes condition can be narrowed down by considering the evaluated features of the mobile applications according to their personal preferences.